2017
DOI: 10.1039/c6dt03854a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic and vibrational properties of Sn2P2Se6and Pb2P2S6crystals and their metallization under high pressure

Abstract: External stimuli enabling either a continuous tuning or an abrupt switching of the basic properties of materials that are utilized in various industrial appliances could significantly extend their range of use. The key characteristics of semiconductors are basically linked to their electronic and optical properties. In this study, we experimentally demonstrated that two kindred wide-band-gap semiconductors, ferroelectric SnPSe and paraelectric PbPS, which are commonly used in optical technologies, have remarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 89 publications
3
13
0
Order By: Relevance
“…6(c)]. 178,179 Similar results were reported for other materials (e.g., Sn 2 P 2 S 6 ). 180 Another potential route to high-pressure thermoelectricity is linked to phase transitions, leading to stabilization of crystal structures with lowered thermal conductivity.…”
Section: Journal Of Applied Physicssupporting
confidence: 78%
See 2 more Smart Citations
“…6(c)]. 178,179 Similar results were reported for other materials (e.g., Sn 2 P 2 S 6 ). 180 Another potential route to high-pressure thermoelectricity is linked to phase transitions, leading to stabilization of crystal structures with lowered thermal conductivity.…”
Section: Journal Of Applied Physicssupporting
confidence: 78%
“…177 It was reported that the application of high pressure can dramatically alter the electrical and thermoelectric properties of these materials [Figs. 6(a) and 6(b)], 178,179 leading to very large increases in their power factors [ Fig. 6(d)].…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, E g has indirect character in both phases. The calculated E g values for the ferroelectric phase and paraelectric are in agreement with the experimental and theoretical values [9,29,46]. In both phases of the Sn 2 P 2 S 6 compound, the E g values as with the results of [46] decrease due to the increase in pressure.…”
Section: Electronic Propertiessupporting
confidence: 82%
“…The calculated E g values for the ferroelectric phase and paraelectric are in agreement with the experimental and theoretical values [9,29,46]. In both phases of the Sn 2 P 2 S 6 compound, the E g values as with the results of [46] decrease due to the increase in pressure. It is understood that the ferroelectric phase of the Sn 2 P 2 S 6 compound at 40 GPa undergoes a phase transition from the semiconductor structure to the semi-metal structure.…”
Section: Electronic Propertiessupporting
confidence: 82%